PROGRAM COMPLEX OF NOISEPROOF REED-SOLOMON ALGORITHM - Білецький, А. Я.; Волівач, О. О.; Якимчук, М. А.; Чалайдюк, С. О. (Science-based technologies, 2011)
The algorithm ofencoding and decoding text fileby Reed-Solomon has been considered in the article. The proposed method of encoding-decoding of RSis optimal, effective and efficient algorithmforcorrecting errorsindata blocks.The structure of the processof reception and transfer ofinformation was investigated.This algorithmis implemented in the environment ofC++, Qt.